Reviving Bultmann's Theological Thought Anew in the Contemporary Context - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (Tumou Tou, 2025)
This article aims to refresh the theological thought of Rudolf Bultmann in a contemporary context by examining his contributions to existential theology and the relevance of the Gospel in the modern era. The main focus of this study includes Bultmann's ideas on the “Hidden God”, divine revelation, and existential faith experience, as well as the concept of demythologisation as an attempt to actualise the biblical message in an increasingly secular and pluralistic world. Criticism of his hermeneutical methods is also discussed to evaluate the relevance of Bultmann's theology in confronting the challenges of spiritual life and contemporary Christian ethics. The research demonstrates that, despite facing criticism, Bultmann's thought remains relevant and offers new insights into understanding faith, revelation, and Christian dogma in the modern world. Thus, this article presents a perspective of renewal in the application of Bultmann's theological thought for the contemporary context.